FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI HOME INDUSTRI TAPE DI DESA BANJARSARI - Ayu Setyawati; Dwi Susilowati; M.Sri Wahyudi (Program Studi Ekonomi Pembangunan, 2019)
The purpose of this study is to determine the effect of the amount of capital, labor and raw materials on the production of home industry tape in Banjarsari Village, Ngajum subdistrict, Malang Regency and to determine income home industry tape in Banjarsari village. The number of samples used in this study were 64 respondents. The analysis technique used in this study is multiple linier regression. The result of data analysis showed that capital (X1) with a coefficient of 0.00039, labor (X2) with a coefficient of 5.01381 and raw materials (X3) with a coefficient of 0.00186 had a significant positive effect on the production of the home industry tape in Banjarsari Village. The average gross income of the homeowner of the tape industry is Rp 1.279.500 and the average net income is Rp 647.784 in a single production process.